Eurozone Between Optimality, Viability and Perennity - Vigneron, Philippe (DEMO, 2017)
The Euro area cannot certainly be considered as an optimum currency area but is this determinant to propose to bring it to an end and to come-back to national currencies ? Th e euro area showed that it could be considered as a viable monetary area as it exists since more than 15 years. Th e aim of this article is to know if it could be perennial and to do so on which bases its functionning could be enhanced.(original abstract)
Keywords: Eurozone; International monetary system; Currency areas; Currency systems; Economic and Monetary Union (EMU)